Integration of the Total Physical Response (TPR) Method and the Feedback Method in Minimizing Phonological Interference of the Arabic Language / Integrasi Metode Total Physical Response (TPR) dan Metode Umpan Balik (Feedback) dalam Meminimalisir Interferensi Fonologi Bahasa Arab - Mukhtarini, Amy Shelawah; Zein, Umar Najih; Muhajir, Muhajir; Robihah, Anti Tazkiyatur; Oktavia, Eka (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study aims to analyze phonological interference in Arabic language learning and to formulate an effective strategy through the integration of the Total Physical Response (TPR) method and feedback. This research employs a qualitative approach using a library research design. The focus is on learners in Islamic schools, namely Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA), who are generally at beginner to intermediate levels with Indonesian as their first language. The findings indicate that phonological interference is influenced by differences in sound systems, articulatory habits (muscle memory), and psychological factors such as language anxiety. The integration of TPR and feedback is effective in minimizing pronunciation errors through cognitive, motor, and affective approaches. In the comprehension phase, recast is used, while in the production phase, explicit corrective feedback is more effective, with metalinguistic feedback serving as reinforcement. This study proposes the TPR-F model as an adaptive, systematic, and contextual procedure for teaching Arabic phonology in Islamic school settings.Penelitian ini bertujuan menganalisis interferensi fonologi dalam pembelajaran bahasa Arab serta merumuskan strategi melalui integrasi metode Total Physical Response (TPR) dan feedback. Penelitian ini menggunakan pendekatan kualitatif dengan jenis library research. Fokus kajian diarahkan pada pembelajar di MI, Mts, dan MA, yang umumnya berada pada tingkat pemula hingga menengah dengan latar belakang bahasa ibu bahasa Indonesia. Hasil penelitian menunjukkan bahwa interferensi fonologi dipengaruhi oleh perbedaan sistem bunyi, kebiasaan artikulatoris (muscle memory), serta faktor psikologis seperti language anxiety. Integrasi TPR dan feedback efektif meminimalisir kesalahan pelafalan melalui pendekatan kognitif, motorik, dan afektif. Pada fase pemahaman digunakan recast, sedangkan pada fase produksi explicit corrective feedback lebih efektif, dengan metalinguistic feedback sebagai penguatan. Penelitian ini menghasilkan model TPR-F sebagai prosedur pembelajaran fonologi yang adaptif, sistematis, dan kontekstual dalam pembelajaran bahasa Arab di madrasah.